Addressing Plastic Waste in Bali, Indonesia: Learning from Global NGO Initiatives and Government Policies - Runtukahu, Yusuf Eddo; Manap, Yusril Sudiro Abdul; Hendriarto, Steve; Utomo, Romualdus Nugraha Catur (ECOTAS, 2025)
Global plastic production has exceeded 300 million tons annually since 2014, driven by their durability, versatility, and low cost. However, plastic pollution has become a major issue, particularly affecting freshwater and marine ecosystems. Bali, a popular tourist destination in Indonesia, suffers from severe plastic pollution due to high tourist numbers and inadequate waste management. This review highlights the urgent need to adopt successful NGO models and technologies while implementing comprehensive policies and enhancing public awareness. Addressing not only the consumption phase but also production and post-consumption phases is crucial. Accelerating recycling technology and facility development through the formal sector is essential. A circular economy approach, supported by key stakeholders, is vital for improving plastic waste management in Bali. Effective waste management is crucial for environmental preservation and the long-term sustainability of Bali's tourism industry, which is key to its economic future.